2020
DOI: 10.3390/agronomy10111627
|View full text |Cite
|
Sign up to set email alerts
|

Response to Salt Stress in Lettuce: Changes in Chlorophyll Fluorescence Parameters, Phytochemical Contents, and Antioxidant Activities

Abstract: Chlorophyll fluorescence (CF), growth parameters, phytochemical contents [proline, chlorophyll, ascorbic acid, total phenol content (TPC), total flavonoid content (TFC)], and antioxidant activities were investigated in lettuce (Lactuca sativa L.) seedlings grown under different sodium chloride (NaCl) concentrations (0, 50, 100, 200, 300, and 400 mM) in a controlled environment for eight days. The parameters were evaluated at two days intervals. Almost of the CF and growth parameters as well as phytochemicals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
52
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 57 publications
23
52
1
2
Order By: Relevance
“…As a contrast result, salinity stress slightly increased chlorophyll content in some barley seedlings. This finding is agreement with the results reported in cotton (Higbie et al 2010), sunflower (Heidari et al 2014, Thellungiella sals (Goussi et al 2018), and lettuce (Shin et al 2020). It has been reported that increasing salt solutions in leaf tissue decreases leaf area index and leads to increase in specific leaf weight (Sohan et al 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a contrast result, salinity stress slightly increased chlorophyll content in some barley seedlings. This finding is agreement with the results reported in cotton (Higbie et al 2010), sunflower (Heidari et al 2014, Thellungiella sals (Goussi et al 2018), and lettuce (Shin et al 2020). It has been reported that increasing salt solutions in leaf tissue decreases leaf area index and leads to increase in specific leaf weight (Sohan et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Chlorophyll as a green-colored pigment is a vital component of the photosynthetic apparatus, and its role in capturing light energy, energy transduction, and stabilization of membranes has been investigated extensively (Porcar-Castell et al 2014;Shah et al 2017;Shin et al 2020;Abrar et al 2020). The relative chlorophyll content is likely to decline under salt treatment compared with control condition.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors can influence optical properties of chlorophyll as well as other pigments, making the overall absorption, reflectance and fluorescence signals of plants and leaves to act as valuable intrinsic biomarkers exploitable for various studies. Investigations can vary from the basic mechanisms of photosynthetic processes to the noninvasive characterization of leaf growing or plant adaptation to stress inducing factors such as changes in light irradiation and soil components, for applications ranging from industry and farming to environmental surveillance [25][26][27][28].…”
Section: Figurementioning
confidence: 99%
“…Moreover, an electrical conductivity of 3.8 and especially 4.8 mS cm −1 in the nutrient solution was able to enhance the properties of fresh-cut lettuce, reducing respiration, browning phenomena, the decay process, and prolonging its shelf life [32]. Therefore, while a mild salinity, 5 mM < [NaCl] < 30 mM, can exert beneficial effects with a minimal impact on lettuce growth and biomass, high salinity concentrations (NaCl > 30 mM) can limit plant growth and development by affecting ions and water uptake, thus causing oxidative stress with a consequent negative impact on photosynthesis, growth/yield, and quality [33]. Obviously, a low NaCl concentration (NaCl~5mM), does not affect growth and biomass and does not elicit a defence response [34].…”
Section: Introductionmentioning
confidence: 99%